Design Investigation of 5 kW Organic Rankine Cycle (ORC) System Using Diffusion Absorption Refrigeration (DAR) for Cooling and Power Generation for India - Pathak S.; Shukla S.K. (My University, 2025)
A country like India has great potential for the conversion of waste heat into power through Organic Rankine Cycle (ORC). This paper focuses on the design feasibility of a method to produce combined power and cooling effect through ORC, which is environment friendly as it adds no emission for the environment. The organic fluid R123 has been selected for organic Rankine cycle. The working fluid R123 has very low ODP (ozone depletion potential of 0.02) and GWP (global warming potential of 77). The electrical power output and power output of expander are 5 kW and 5.26 kW respectively. The source temperature for ORC is 130. At the outlet of the evaporator the temperature of heat transfer fluid is 110. This available heat at the evaporator outlet act as heat input for diffusion absorption refrigeration (DAR) system. The working fluid for this system is selected as NH 3 -LiNO 3 -He, which operates at lower generator temperature. The evaporator temperature of DAR system is achieved around 5 also the cooling capacity produced around 2.5 kW. This combined system satisfies both cooling and power requirement simultaneously and make a system in uncoupled form. Further, the analysis of the efficiency of ORC system in variable condensing temperature has been done under Indian climatic conditions. The study reveals that with the increment in the ambient temperature condensing temperature increases. The performance of ORC degrades with the increment in condensing temperature. The cooling water from cooling tower passes from the evaporator of DAR system. This leads to decrease in the cooling water temperature from 23.5 to 15.5. The condensing temperature decreases from 35 to 32 due to the temperature reduction of cooling water. In turn, the efficiency of ORC system increases by approximately 7%. This combined system meets the demand of both power production and cooling effect with no emission of pollutants to the environment. © 2019 IOS Press. All rights reserved.